Modulating influence of cytochrome P-450 MspI polymorphism on serum liver function profiles in coke oven workers. Issue 3 (1st March 1999) - Wu, M T; Ho, C K; Huang, S L; Yeh, Y F; Liu, C L; Mao, I F; Christiani, D C
Abstract : OBJECTIVES: It was reported previously that topside oven workers with heavy exposure to coke oven emissions had increased serum activities of hepatic aminotransferase in one coke oven plant. This study was conducted to investigate the modifying effect of CYP1A1 MspI polymorphism on liver function profiles in coke oven workers. METHODS: 88 coke oven workers from a large steel company in Taiwan were studied in 1995-6. Exposure was categorised by work area: topside oven workers and sideoven workers. Liver function profiles including serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), r-glutamyl transpeptidase (GGT), alkaline phosphatase (ALP), and total bilirubin (BIL) were examined in the morning after personal exposure measurements. The MspI polymorphism was determined by polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP). RESULTS: Five of 23 (22%) topside oven workers and seven of 65 (11%) sideoven workers had the CYP1A1 MspI homozygous variant genotype. With sideoven workers with the combined wild type and heterozygous variant as the reference group in multiple regression models, it was found that topside oven workers with the combined traits had mean AST and ALT activities that were 21% and 46% higher (95% confidence interval (95% CI) 4% to 42% and 12% to 91%, respectively) than the reference group after adjusting for appropriate confounders. Also, topside oven workers with the homozygous variant trait had mean AST, ALT, and GGT activities that were 59%, 68%, and 157% higher (95% CI 21% to 109%, 6% to 168%, and 39% to 374%, respectively) than the reference group. The prevalence of an abnormal hepatocellular pattern (AST > 37 IU/l or ALT > 39 IU/l) was more common in the topside oven workers with the homozygous variant than in the sideoven workers with the other combined genotypes (adjusted odds ratio 9.9, 95% CI 1.2 to 82.3) after adjusting for appropriate confounders. CONCLUSIONS: The CYP1A1 MspI polymorphism may modify the biotransformation of coke oven emissions, which results in hepatocellular damage in coke oven workers.